Efeito do chorume de suínos e do ph do solo sobre o tombamento de pepino causado por Pythium sp - Manteli, Claudia (2010)
Among the soilborne plant pathogens, the Pythium sp. is one of the most aggressive and difficult to control and affects several crops. In the culture of cucumber (Cucumis sativus L.) causes collar rot and subsequent damping-off. Control of this pathogen is based on cultural alternatives for the chemical treatment of seed not be effective. The addition of organic compounds promotes chemical changes in soil physical and biological and nutritional changes in plants. The swine manure is presented as an alternative to control this pathogen due to its availability and its nutritional potential. However, soil pH influences the release of different compounds by swine manure and consequently in its action on pathogens. For the genus Pythium, there are no reports of use of swine manure as an alternative control applied at different levels of soil pH. This study evaluated the effect of swine manure in soil with different pH levels on disease control on the development of the pathogen and its influence on chemical and biological soil. Three different situations were tested, and all maintained in the application of 0, 5, 10 and 15% manure. In experiments with randomized arrangement. In Petry plates, evaluated the implementation of the volumes of swine manure in soil with pH 4.8, 6.3 and 8.4, 1, 2 and 3 days of incubation on the mycelial growth of Pythium sp. In soil with pH 8.4 the growth of colonies was higher in all periods tested, and soil pH 4.8 and 6.3 with up to two days of development, the colonies had inhibited growth. In randomized experiments, with incubation hermetic same volumes of swine manure, for four days in soil with pH 4.8, 6.3 and 8.4, we obtained a smaller rate of damping of plants in soil pH 4.8. In another situation, it was evaluated in experiments with randomized block the effect of different amounts of swine manure on the registration of cucumber plants in pots. The application of soil with two different pH levels (pH 4.8 and 6.3) revealed a lower number of cucumber plants having fallen to the ground with pH 4.8. In all cases, the antifungal effect of volatile fatty acids, released by swine manure, when applied to soil with higher acidity level, he was appointed as the main cause of getting these results.